Contemporary Misticism: Recovering Sensible Aesthetics in an Age of Digital Production - Schepen, Van (Religions, 2019)
Materialist accounts of artistic development emphasize the ongoing revolution of media in the progress of history. Amongst the most popular accounts of modernity are Walter Benjamin's essays on the relationship of photography to traditional art. His account of the loss of aura has been subject to countless reinterpretations since its publication. The present essay addresses the contemporary production of a number of architects and artists whose work provides an interesting challenge to the Benjaminian account of the secularization of artistic ritual. The artists Adam Fuss, Vera Lutter, Alison Rossiter, Sally Mann, and others have recently been exploring photographic methods that contradict the Benjaminian account of the history of photography. They continue to explore techniques that Benjamin placed in the auratic pre-paper-print era, such as Daguerreotypes and photograms, as well as employing other more material/chemically based effects. Such artistic choices are often considered nothing more than a nostalgic reverie trying to stem the tide of materialist history, a flawed search for a lost aura of presence. However, when these works are set against the backdrop of contemporary digitized production and of the Dusseldorf School as well as most other contemporary photographers, these "retro" works stand as a critical counterpoint to our present seamless digital imperium. The soft and hazy effects of these works, what I am calling their misticism, occludes the particularity of digital bits of information in a search to connect to the material and the sensual, something denied by information-saturated technologies. Even within a materialist approach to history, there is room to view these architectural and artistic effects as critically productive rather than merely retrograde. The present essay argues for the timely relevance of contemporary retro-photographic techniques in fostering both a critical attitude and as evidence of attempts to recover a sense of spiritual presence.